PENGARUH UMUR KEHAMILAN, TINGKAT PENGETAHUAN TENTANG MENYIKAT GIGI, TERHADAP DERAJAT KEBERSIHAN GIGI DAN MULUT PADA IBU HAMIL DI KELURAHAN BINTORO KABUPATEN DEMAK - Bedjo Santoso; Bambang Sutomo (JURNAL KEBIDANAN, 2017)
In order to realize the development of health, oral health as an integral part of the whole human health. Pregnant women are one of the vulnerable groups care of oral health care. In the event of pregnancy, occurring patterns of change in the maintenance of oral hygiene becomes worse. These changes are caused by hormonal changes that marked the onset of nausea, vomiting, feeling of fear when brushing your teeth. The results of a preliminary study on 10 pregnant women in Sub Bintoro randomly during routine activities posyandu average values obtained OHI-S is 3.3 (poor category). It also obtained data indicating maternal knowledge about how to brush teeth still low. This study aims to determine the effect of gestational age, the level of knowledge about brushing teeth, the degree of oral hygiene in pregnant women in Sub Bintoro.This type of research is quantitative descriptive cross sectional survey research approach. The population of pregnant women Bintoro Village, District Demak, Demak which amounted to 80 people. Sampling was done Proportional stratified random sampling method, a number of 55 people. The data were analyzed by descriptive quantitative, with the Spearman rank correlation test, regression test sdan with linear regression.The results showed maternal gestational age mostly in the third trimester of 29 people (52.7%), the level of knowledge in good condition category 40 people (60.6%), the degree of oral hygiene pregnant women mostly in the category of OHI-S are 25 persons (37.9%). There is a significant relationship between the degree of knowledge of dental and oral hygiene, according to the results with the Spearman rank correlation test with CI 95% (α = 0.05), obtained p.value = 0.000. There is a significant effect on the degree of knowledge of dental and oral hygiene, according to the results of linear regression test with CI = 95% (α = 0.05), obtained p.value = 0.000. Pregnant women are advised to maintain and increase the maintenance of dental hygiene at all stages of gestation, following the extension of activities by health personnel, maintaining and improving ways of maintaining oral hygiene.